Food quality balancing health and disease - Holban, Alina Maria (Handbook of food bioengineering, 2018)
Food Quality: Balancing Health and Disease, Volume Thirteen in the Handbook of Food Bioengineering series, provides essential information for researchers, scientists and students on the relationship between the quality of foods and disease at the biological level. It presents different technological approaches to detect food properties and their capabilities for balancing health and disease to deliver high-quality products to consumers. This volume explores the dynamic potential of how food bioengineering can improve traditional foods through modern methods to make a positive impact on human health and foster innovation.--Provided by publisher.